Time in Therapeutic Range for Left Ventricular Assist Device Patients Anticoagulated With Warfarin: A Correlation to Clinical Outcomes. Issue 1 (January 2017) - Halder, Laura C.; Richardson, Laura B.; Garberich, Ross F.; Zimbwa, Peter; Bennett, Mosi K.
Abstract : Left ventricular assist devices (LVADs) require anticoagulation therapy with vitamin K antagonists to reduce the risk of thrombotic events. The quality of anticoagulation may be assessed by the time in therapeutic range (TTR). We analyzed a retrospective cohort of LVAD patients at a single institution from January 2012 to September 2014. Primary outcomes included TTR during the study time period and TTR 30 days preceding a bleeding or thrombotic event. Fifty-one patients (mean age 57.0 ± 14.6 years; 78% male) had an overall TTR of 52%. Median international normalized ratio (INR) preceding a bleeding and thrombotic event was 2.7 and 2.2, respectively ( p = 0.049). In the 30 days before an event, patients with a bleeding event were more likely to be on low-dose aspirin (37% vs . 12%; p = 0.018) and spend a higher proportion of time above therapeutic range (41% vs . 17%; p = 0.007) compared with those with thrombotic events. The association between a greater percentage of time above therapeutic range in the 30 days before a bleeding event demonstrates the importance of avoiding a supratherapeutic INR in the LVAD patient population and the usefulness of TTR as a measure of the overall quality of anticoagulation and monitoring in an LVAD cohort. Abstract : Supplemental Digital Content is available in the text.